2022
DOI: 10.1155/2022/1442613
|View full text |Cite
|
Sign up to set email alerts
|

Fludarabine/Cyclophosphamide Conditioning Regimen in Aplastic Anemia Patients Receiving Matched-Sibling Donor Transplant Is Non-inferior to ATG/Cyclophosphamide: A Single-Center Experience from Pakistan

Abstract: The successful outcome of allogeneic hematopoietic stem cell transplant (HSCT) in aplastic anemia patients is driven by suitable donor selection, appropriate conditioning regimen, early intervention, and optimal supportive care after transplant. Pakistan, being a developing country, faces grave economic challenges due to meager health care budget; therefore, cost constraints remain the foremost impediment in optimizing transplant facilities for socioeconomically deprived patients. We conducted a single-center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Approximately one-third of these patients can receive stem cell transplant as a cure. Fludarabine-based conditioning along with antithymocyte globulin (ATG) and cyclophosphamide has emerged as a promising alternate regimen with excellent results where Chaudhry et al [ 11 ] and Zaidi et al [ 12 ] have reported an OS of 84% and 76%, respectively. As evident in the literature, the prevalence of aplastic anemia in the Asian population is 3 times higher as compared to Western countries with environmental contaminants such as benzene, arsenic, and other pesticides providing an increased predisposition in the country [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately one-third of these patients can receive stem cell transplant as a cure. Fludarabine-based conditioning along with antithymocyte globulin (ATG) and cyclophosphamide has emerged as a promising alternate regimen with excellent results where Chaudhry et al [ 11 ] and Zaidi et al [ 12 ] have reported an OS of 84% and 76%, respectively. As evident in the literature, the prevalence of aplastic anemia in the Asian population is 3 times higher as compared to Western countries with environmental contaminants such as benzene, arsenic, and other pesticides providing an increased predisposition in the country [ 13 ].…”
Section: Discussionmentioning
confidence: 99%